Laicità e partecipazione politica (Stato, Chiese e pluralismo confessionale, 2024)
Legal secularism and political participationABSTRACT: As is well known, the Italian term ‘laicità’ is polysemic and cannot be adequately translated into English. The word ‘secularism’, in fact, only captures certain senses of ‘laicità’. Ultimately, we are dealing with a very complex phenomenon that surely cannot be analyzed with a dichotomic black and white concept. In this paper we are mainly interested in highlighting legal secularism, understood as neutrality. However, we must pay attention to the fact that liberal neutrality, understood as mutual tolerance and impartiality of institutions, is a “committed neutrality” which deeply differs from Max Weber’s uncommitted neutrality to which scientists aspire. On the other hand, the ideal of legal secularism comes into harsh conflict with the partisan spirit that characterizes political life. Democracy is not only respect for rules, but must come to terms with the citizens’ variegated senses of belonging to this or that community. As they say: “My country, right or wrong”. Precisely because of these limits to rational discourse, we believe that legal secularism, in a broad sense, is not fully achievable even in an open society.SOMMARIO: 1. L’individuazione del tema che verrà affrontato - 2. Laicità, una nozione complessa - 3. (segue) Tre concetti di laicità - 4. (segue) La neutralità degli scienziati e la neutralità delle istituzioni laico-liberali - 5. (segue) La così detta “scienza del diritto”: un ideale sulla via del tramonto - 6. Partecipazione e appartenenza - 7. (segue) Il fascino duraturo della democrazia diretta e la ritrosia del laico - 8. (segue) Il successo delle argomentazioni fallaci quale fenomeno collettivo - 9. Concludendo: i pregi e i limiti della ragione laica.